Measurement of the top quark pair production cross section in pp̄ collisions using multijet final states - Abbott, B; Abolins, M; Abramov, V; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amos, N; Anderson, E; et al. (1999)
We have studied tt̄ production using multijet final states in pp̄ collisions at a center-of-mass energy of 1.8 TeV, with an integrated luminosity of 110.3 pb-1. Each of the top quarks with these final states decays exclusively to a bottom quark and a W boson, with the W bosons decaying into quark-antiquark pairs. The analysis has been optimized using neural networks to achieve the smallest expected fractional uncertainty on the tt̄ production cross section, and yields a cross section of 7.1±2.8 (stat)±1.5 (syst) pb, assuming a top quark mass of 172.1 GeV/c2. Combining this result with previous DØ measurements, where one or both of the W bosons decay leptonically, gives a tt̄ production cross section of 5.9±1.2 (stat)±1.1 (syst) pb. ©1999 The American Physical Society.